Profile and vocational of the professional in school libraries in Brazil, Spain and Portugal - Lopes Fujita, Mariângela Spotti [UNESP]; Carmen Agustín-Lacruz, Maria Del; Lúcia Terra, Ana (My University, 2018)
The main objective of this work is to know in detail the professional profile of school librarians in Brazil, Spain and Portugal. Three specific objectives were defined: a) to identify and describe the functions and tasks performed by these professionals; B) to determine the number of working hours devoted to school library management and c) to know school librarians initial and continuous training. For this purpose, an analysis of relevant literature and legislation was carried out in addition to data collection on a librarians' sample from the three countries, using a survey questionnaire. The main objectives achieved include the detailed characterization of the professional profiles of school librarians in Brazil, Spain and Portugal, identifying work and functions of schools librarians, the kind of education they have and the level attained. Areas and matters in which they are engaged in professional terms, the formal and continuous training they have, and the number of hours devoted to the school library are also presented.
Perfil e formaÇÃo do profissional em bibliotecas escolares no Brasil, Espanha e Portugal
Keywords: Professional profile; School libraries; Vocational training